Implementation of the Child-Friendly School Program in Fostering Students’ Character Development at the Elementary School Level - Abas, Nilawati (Universitas Negeri Padang, 2026)
Educational institutions are expected to provide a safe, inclusive, and supportive learning environment for students. The Child-Friendly School (CFS) program was introduced as an educational policy to ensure the fulfillment of children’s rights at school. However, previous studies have often discussed CFS from a normative perspective, with limited analysis of its practical implementation and its contribution to students’ character development. This study aims to analyze the implementation of the Child-Friendly School program, identify challenges encountered, and examine strategies to foster students' character development. This research adopts a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and document analysis involving education officials, school principals, teachers, students, parents, and school committees. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data credibility was ensured through source and method triangulation. The findings reveal that the implementation of the Child-Friendly School program is reflected in six key indicators: child-friendly policies, curriculum integration, teachers and educational staff trained in children’s rights, adequate facilities and infrastructure, active student participation, and parental involvement. The program's implementation contributes positively to students' character development, particularly in fostering discipline and nationalism. These results indicate that the Child-Friendly School program functions not merely as an administrative policy but as a strategic approach to strengthening students' character in elementary education.